Attachment to Parents As a Moderator in the Association between Sibling Bullying and Depression or Suicidal Ideation among Children and Adolescents - Bar-Zomer, Jasmin; Brunstein Klomek, Anat (Frontiers in Psychiatry, 2018)
Bullying is one of the most widespread phenomenon in childhood and adolescence. Interestingly, most research on bullying focuses on bullying at school and not on bullying among siblings at home. Sibling bullying is the most frequent form of repeated aggression that children experience in their lifetime. Further, previous studies indicate that sibling bullying is associated with depression and self-harm behavior. However, the association between sibling bullying and suicidal ideation was never previously examined. Attachment to parents is one variable that can moderate the association between sibling bullying and depression/suicide ideation. To our knowledge there is no existing study that examines the association between sibling bullying and attachment patterns. In addition, no previous study has examined the moderating role of attachment on the association between sibling bullying and depression or suicidal ideation among adolescents. The current study includes 279 Israeli students aged 10-17 (M=13.5; SD=1.98; 164, 58.8% females) whom completed self-report questionnaires regarding school and sibling bullying, attachment to mother and father, depression and suicidal ideation. The results indicated an association between bullying among siblings and school bullying. In addition, children and adolescents who were consistently involved in sibling bullying were at greater risk for depression and suicide ideation when compared to children and adolescents who were not involved in sibling bullying. A secure attachment to one’s father (but not to one’s mother) moderated the association between sibling bullying and depression/suicide ideation. It should be noted that when suicide ideation was examined above and beyond depression, attachment to one’s father did not moderate the association between sibling bullying involvement and suicide ideation. This finding indicates that depression plays a central role in the association between sibling bullying and suicide ideation. These results suggest that sibling bullying is a risk factor for depressive symptoms and suicide ideation and that secure attachment to one’s father may serve as a protective role. Future bullying prevention programs should include sibling bullying and encourage the increased availability of paternal emotional support. Other theoretical and applied implications for prevention of both sibling bullying and suicide are discussed.